FAKTOR-FAKTOR PENGHAMBAT MASYARAKAT DAERAH TERTINGGAL MEMPEROLEH PENDIDIKAN FORMAL (Studi Kasus Jorong Bukit Lintang Nagari Malampah Kecamatan Tigo Nagari Kabupaten Pasaman) - Misrida aini; yurni suasti; fitriana Syahar (DEPARTEMEN GEOGRAFI FIS UNP, 2017)
This is a qualitative descriptive, which aims to describe the inhibiting factors of the underdeveloped regions of society to obtain formal education and to know the extent to which the role of local government / community institutions in community education lags behind in Jorong Bukit Lintang. The technique of selecting the informants was conducted by snowball sampling, with 40 informants, and to answer the questions from the role of government / community institution in Jorong Bukit Lintang education, the researcher chose the key informants, namely Head of Education Office of Pasaman, village head Malampah, Jorong Bukit Lintang, Teachers who teach in Jorong Bukit Lintang and community leaders in Jorong Bukit Lintang. Technique of taking data with observation, interview and documentation. Furthermore, the technique of data validity analysis is done by using triangulation technique by obtaining data from research subjects at different times, places and situations. Based on the findings in the field, the results of this study are as follows: 1) The factors that inhibit the lagging local communities Jorong Bukit Lintang obtain formal education that is, a) The low views of the people of the disadvantaged areas in Jorong Bukit Lintang on the importance of education, b) Lack of transportation and destruction of Jorong Bukit Lintang public road infrastructure facilities to formal education facilities, c) Low interest of children for schools, d) Children play a very important role in meeting the needs of families, in mangarap fields and fields, especially for people who have large land. 2) Lack of school facilities and infrastructure in Jorong Bukit Lintang, and the declining role of government and community institutions on the advancement of education of disadvantaged areas in Jorong Bukit Lintang become the inhibiting factor for Jorong Bukit Lintang people get formal education.